Peranan Pemimpin Informal Dalam Mengatasi Masalah Sosial Kemasyarakatan - Kamaruddin Tone (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2012)
Informal leaders are community leaders. Right in the figure because they have influence or authority or charisma in front of the community. Community leaders can perform the role of social control against their peoples. For example, in a way to educate, advise, guide, nurture, admonish, and so in order to comply with their peoples values - values and norms. an effort to create a society that is free from injustice or social dysfunction . Achievement of educational goals multukultural success in society is influenced by the functioning of the informal leader. Informal leaders have influence and strategic position in creating a harmonious community life - humanist. Therefore, informal leaders need to run a variety of multicultural education approach optimally as individuals who play an active role in providing education mutlikultural in society. The function of a leader is not going to be achieved if the cultural capacity of the informal leaders can not be realized. Therefore, the cultural capacity needs to be developed through various interventions.